Association between Serum and Salivary Uric Acid in Periodontitis Patients with and Without Metabolic Syndrome - Uppin, Rabiya Basari (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Currently, there is limited research on the correlation between Metabolic status and serum and salivary UA in periodontitis patients. Objectives: The objective of this study is to evaluate the relationship between serum and salivary uric acid (UA) levels in periodontitis patients with and without metabolic syndrome (MetS). Materials and Methods: This cross-sectional study included 156 periodontitis patients (with MetS = 78 and without MetS = 78) receiving routine blood investigations in a private diagnostic center in Bidar, Karnataka. Personal characteristics and MetS components, such as systolic and diastolic blood pressures, were recorded. Blood parameters such as glycated hemoglobin, total cholesterol, high-density lipoprotein, triglycerides, low- density lipoprotein, serum UA, and salivary UA were determined using a biochemical analyzer. Periodontal variables of plaque index, gingival index, probing pocket depth, and clinical attachment loss were recorded. An independent t-test and analysis of variance, followed by Tukey’s tests, were applied to compare the serum and salivary UA between MetS-positive and MetS-negative patients and the severity of periodontitis. Results: MetS- positive patients showed significantly raised serum UA (6.04 vs. 5.44, P < 0.001) and salivary UA (5.51 vs. 3.84, P < 0.001) compared to MetS-negative individuals. MetS-positive patients revealed a significant difference in serum UA levels (F = 88.432, P < 0.001) and salivary UA levels (F = 22.428, P < 0.001) across different severities of periodontitis. In contrast, MetS-negative patients showed no significant difference in serum UA (F = 1.216, P = 0.302) and salivary UA (F = 0.576, P = 0.565) based on the severity of periodontitis. Conclusion: Presence of MetS is associated with higher serum and salivary UA levels in individuals with periodontitis. The differences in UA levels by severity of periodontitis suggest that UA may play distinct roles in systemic and local inflammation.